EFL Learners Belief about Vocabulary Learning - Mustari, Mustari; Effendi, Rezhi (IAIN KENDARI, 2024)
This study aims to determine the beliefs of EFL students about vocabulary learning. The data was taken from 20 students of an English Education Study Program at a University in the second semester of the 2019/2020 academic year. Qualitative data is the design of this study using a reflective journal as instrument. The result of study reveals how the students' beliefs about vocabulary learning are; learners’ reactions in vocabulary, learners’ belief about difficulties in learning vocabulary, learners’ belief of proficiency in vocabulary learning, learners’ belief on the benefits of vocabulary learning, learners’ belief on strategies in vocabulary learning, learners’ belief of perceived confidence used English in communication. These research methods use descriptive data analysis techniques. Furthermore, this study would provide information to readers about the importance of knowing the beliefs of EFL students so that students can improve their skills in learning vocabulary.Keywords: EFL learners, vocabulary learning, learner’s belief